Experimental investigation of the thermosiphonic phenomenon in domestic solar water heaters - Kalogirou, Soteris A.; Panayiotou, Gregoris; Florides, Georgios A.; Roditis, George; Katsellis, Nasos; Constantinou, Andreas; Kyriakou, Paraskevas; Vasiades, Yiannis; Parisis, Thomas; Michaelides, Alexandros; Nielsen, Jan Erik (My University, 2013)
The deeper understanding of the ‘thermosiphonic phenomenon’ and the identification of the key parameters affecting it, is the main aim of a research project currently in process in Cyprus. In this work a review of the existing standards and scientific knowledge concerning domestic solar water heaters is presented. The first preliminary results of the experimental investigation of the ‘thermosiphonic phenomenon’ in domestic solar water heaters are also presented. For this purpose a special test rig was set up and equipped with all sensors necessary to measure all parameters that are most likely to affect the ‘thermosiphonic phenomenon’. All tests were conducted according to ISO 9459- 2:1995(E). At first, the solar collector was tested according to EN12975-2:2006 in order to determine the thermal performance characteristics at a flow and operation conditions specified by the standard. Consequently, the efficiency of the collector operating thermosiphonically was calculated based on quasi-dynamic approach. Finally, a series of correlations were attempted using the data acquired when the collector is operating themosiphonically which are the following: (i) the temperature difference of the water at the outlet and the inlet of the collector (ΔΤ) with the solar global radiation, (ii) the water mass flow with the solar global radiation, (iii) the water mass flow with the temperature difference of the water at the outlet and the inlet of the collector (ΔΤ). The results of the data analysis showed that these parameters are very well correlated between them since the coefficient of determination (R2) is over 0.91 in all cases.
Keywords: Cyprus; Solar water heaters; Thermosiphonic phenomenon